2008
DOI: 10.1172/jci32519
|View full text |Cite
|
Sign up to set email alerts
|

β3-adrenergic receptor activation increases human atrial tissue contractility and stimulates the L-type Ca2+ current

Abstract: β 3 -adrenergic receptor (β 3 -AR) activation produces a negative inotropic effect in human ventricles. Here we explored the role of β 3 -AR in the human atrium. Unexpectedly, β 3 -AR activation increased human atrial tissue contractility and stimulated the L-type Ca 2+ channel current (I Ca,L ) in isolated human atrial myocytes (HAMs). Right atrial tissue specimens were obtained from 57 patients undergoing heart surgery for congenital defects, coronary artery diseases, valve replacement, or heart transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(116 citation statements)
references
References 68 publications
(95 reference statements)
6
99
4
1
Order By: Relevance
“…Though being the lowest in abundance, the expression of ADRB3 mRNA in the heart of sheep was comparable with the studies reported by Chamberlain et al (1999) and Skeberdis et al (2008) in humans and by Evans et al (1996) in rats. The function of ADRB3 in the heart includes increasing the contractility of myocardial tissue as indicated in studies of patients with heart failure (Moniotte et al, 2001;Morimoto et al, 2004) and dogs with pacing-induced heart failure (Cheng et al, 2001).…”
Section: Discussionsupporting
confidence: 86%
“…Though being the lowest in abundance, the expression of ADRB3 mRNA in the heart of sheep was comparable with the studies reported by Chamberlain et al (1999) and Skeberdis et al (2008) in humans and by Evans et al (1996) in rats. The function of ADRB3 in the heart includes increasing the contractility of myocardial tissue as indicated in studies of patients with heart failure (Moniotte et al, 2001;Morimoto et al, 2004) and dogs with pacing-induced heart failure (Cheng et al, 2001).…”
Section: Discussionsupporting
confidence: 86%
“…We hypothesized that blocking the breakdown of endogenous cAMP by inhibition of cNMP phosphodiesterase activity could therefore affect NO generation in the plant cell. Animal and plant cNMP phosphodiesterase is sensitive to the inhibitor 1-methyl-3-(2-methylpropyl)-7H-purine-2,6-dione (IBMX) (31,32). Application of IBMX to leaf epidermal peels from WT plants evokes NO generation in the absence of a pathogen signal (i.e., the PAMP LPS) (Fig.…”
Section: Cnmp Cngcs and Immune Signalingmentioning
confidence: 99%
“…[87][88][89][90] Other works reported full inhibition of effects of β-AR agonists in frog and rat ventricular cardiomyocytes by dialyzing cells with 2 to 5 mmol/L Rp-cAMPS, 16 µmol/L PKI (which is >3 orders of magnitude higher than its K i ), 20 µmol/L PKI peptide (PKI [15][16][17][18][19][20][21][22] ; K i =36 nmol/L), [91][92][93] or with 1 µmol/L H-89 applied externally. 94 Although the latter studies used rather high doses of inhibitors, the accumulated data strongly support the view that a major part and possibly all of the β-AR enhancement of cardiac Ca V 1.2 is mediated by activation of PKA.…”
Section: Pka Inhibitors and β-Ar Regulationmentioning
confidence: 79%